Analysis of the Evolutionary Relationship between Species of the New Triatoma pseudomaculata Subcomplex (Hemiptera, Triatominae) and Proposal for the Creation of the Triatoma costalimai Subcomplex - da Silva Masarin, Isabella; de Oliveira, Jader; Visinho Dos Reis, Yago; Ravazi, Amanda; Fernandez Madeira, Fernanda; Cristina Antoniassi Fernandes Tadini, Samanta; Galvão, Cleber; Tercília Vilela de Azeredo-Oliveira, Maria; da Rosa, João Aristeu; Alevi, Kaio Cesar Chaboli (The American journal of tropical medicine and hygiene, 2025)
Triatomines are insects of great importance for public health, as they are vectors of protozoan Trypanosoma cruzi, the etiological agent of Chagas disease. The genus Triatoma is the most representative in number of species and one of the most important from an epidemiological point of view. The Triatoma pseudomaculata subcomplex (composed of the species Triatoma arthurneivai, T. pseudomaculata, and T. wygodzinskyi [from the old subcomplex Triatoma maculata] and Triatoma baratai, Triatoma costalimai, Triatoma deaneorum, Triatoma jatai, and Triatoma williami [from the old Triatoma matogrossensis subcomplex]) was recently proposed based on chromosomal data. Thus, considering that the experimental crossings helped with systematic questions about triatomines, we performed crosses between the species of the T. pseudomaculata subcomplex. Thus, we crossed T. pseudomaculata and Triatoma costalimai to assess the possible presence of interspecific genomic and reproductive compatibility. In addition, based on the molecular data available on GenBank, we performed a phylogenetic systematics study to assess the evolutionary relationship of the species of the T. pseudomaculata subcomplex. Experimental crosses did not result in hybrids, demonstrating that there is a prezygotic barrier established between these species. Based on the above, we confirmed the specific status of T. pseudomaculata and T. costalimai based on the biological species concept. Furthermore, the reproductive incompatibility associated with the phylogenetic systematic analyses demonstrate that T. costalimai does not belong to the T. pseudomaculata subcomplex. Thus, we suggest that the sister species T. costalimai and T. jatai should be grouped into a new subcomplex called T. costalimai.